Emotions and ensuing motor performance are altered by regulating breathing frequency: Implications for emotion regulation and sport performance - Buchanan, Taylor L.; Janelle, Christopher M. (Frontiers in Psychology, 2022)
Breathing interventions have been shown to improve sport performance. Although evidence exists to support the role of perceived arousal as a critical underlying mechanism of breathing interventions, methodological differences in the literature preclude clear understanding of potential contributing factors to the effectiveness of such interventions. Under neutral contexts, we have demonstrated attention, dyspnea, and hindrance may need to be considered as mediators of how breathing frequency affects motor performance. We sought to extend our previous findings to determine how breathing frequency affects motor performance under varying emotional conditions. Participants (N = 35, Mage = 21.68, SD = 2.96; 20 females) performed slow, normal, and fast metronome-paced breathing while viewing pleasant and unpleasant stimuli prior to executing a pinch grip task. Performance was assessed via reaction time (RT), variability (V) and error (AE). Assessment of indices of perceived arousal included measuring heart rate variability (HRV) and a visual analog scale responses. Visual analog scales were also used to assess attention, dyspnea, and hindrance. Repeated measures ANOVAs showed slow breathing increased RT and HRV compared to normal and fast breathing under emotional conditions (all p’s < .05). Hierarchical multiple regression models revealed that decreased breathing frequency predicted increases in RT (β= -0.25, p < 0.05) under pleasant conditions, while predicting increases in HRV for unpleasant conditions (β= -0.45, p < 0.001). Increases in dyspnea (β= 0.29, p < 0.05) and hindrance (β= 0.35, p < 0.01) predicted increases in RT under pleasant conditions, while only increases in hindrance predicted increases in RT under unpleasant conditions (β= 0.41, p < 0.01). Decreases in breathing frequency predicted increases in HRV under unpleasant conditions (β= -0.45, p < 0.001). Overall, our findings suggest under varying emotional contexts breathing frequency differentially affects movement, potentially mediated by factors other than perceived arousal. In addition, these results inform the use of breath regulation as an antecedent emotion regulation strategy.